Cybersecurity and Digital Sovereignty: An Analysis of National Data Governance Capacity in the Global Platform Era: A Literature Review - Laras Fitriani (Asian Digital Governance Problems, 2024)
Purpose: This study examines national data governance capacity in the context of cybersecurity and digital sovereignty across Indonesia, the European Union, China, and India during 2010–2024. The research aims to identify how institutional coordination, regulatory coherence, enforcement effectiveness, technological autonomy, and public trust shape digital sovereignty within the global platform era. Subjects and Methods: This study employed a qualitative systematic literature review combined with critical interpretive synthesis. Data were collected from 76 academic articles, cybersecurity reports, institutional publications, and regulatory documents identified through a PRISMA-based selection process. The analysis applied thematic coding, repeated reading, conceptual integration, and comparative governance analysis to examine recurring governance patterns and institutional contradictions. Results: The findings reveal that digital sovereignty operates as a multidimensional governance capacity shaped by institutional integration, cybersecurity readiness, technological infrastructure, and governance legitimacy. The European Union demonstrates strong regulatory coherence, China exhibits centralized enforcement and technological autonomy, India reflects transitional governance adaptation, while Indonesia faces governance fragmentation, technological dependency, and weak cybersecurity preparedness. Conclusions: Effective digital sovereignty requires integrated governance systems, sustainable technological investment, institutional coordination, and long-term public trust in digital governance.